2020
DOI: 10.1038/s41398-020-01023-w
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol-induced inhibition of unconditioned stimulus-reactivated fear memory prevents the return of fear in humans

Abstract: Fear memories can be reactivated by a fear-associated conditioned stimulus (CS) or unconditioned stimulus (US) and then undergo reconsolidation. Propranolol administration during CS retrieval-induced reconsolidation can impair fear memory that is specific to the reactivated CS. However, from a practical perspective, the US is often associated with multiple CSs, and each CS can induce a fear response. The present study sought to develop and test a US-based memory retrieval interference procedure with propranolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…We also demonstrated that the effects of post CS retrieval propranolol on heroin seeking are long lasting, suggesting relatively permanent interference with drug memory. Indeed, preclinical and clinical studies have demonstrated that propranolol has the ability to erase maladaptive memories associated with nicotine, cocaine, heroin or fear ( Fricks-Gleason and Marshall, 2008 ; Zhao et al, 2011 ; Xue et al, 2017b ; Deng et al, 2020 ). Thus, there is compelling evidence suggesting that propranolol might have a therapeutic utility in clinical settings and be an attractive candidate for relapse prevention.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the effects of post CS retrieval propranolol on heroin seeking are long lasting, suggesting relatively permanent interference with drug memory. Indeed, preclinical and clinical studies have demonstrated that propranolol has the ability to erase maladaptive memories associated with nicotine, cocaine, heroin or fear ( Fricks-Gleason and Marshall, 2008 ; Zhao et al, 2011 ; Xue et al, 2017b ; Deng et al, 2020 ). Thus, there is compelling evidence suggesting that propranolol might have a therapeutic utility in clinical settings and be an attractive candidate for relapse prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the limitations of targeting CS-induced reconsolidation could be addressed by also targeting US-induced reconsolidation (Luo et al, 2015). Propranolol is capable of disrupting US-induced reconsolidation via beta-adrenergic signaling (Xue et al, 2017a,b;Deng et al, 2020), making this signaling pathway a promising target for the prevention of relapse.…”
Section: Beta-adrenergic Signaling Is a Promising Safe Target For Preventing Relapsementioning
confidence: 99%
“…We used a modified fear acquisition procedure based on our previous studies ( Deng et al., 2020 ; Liu et al., 2014 ; Yue et al., 2018 ). The participants were asked to specify the relationship between different CSs (colored square pictures on the computer screen) and a US (mild electric shock to the wrist).…”
Section: Methodsmentioning
confidence: 99%